2016
DOI: 10.18632/oncotarget.8770
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative serum CA125, CA19-9 and CEA in gastric carcinoma

Abstract: The prognostic significance of preoperative serum CA125, CA19-9 and CEA in gastric carcinoma (GC) has been widely reported and is still under debate. Here, we evaluated the prognostic significance of preoperative serum CA125, CA19-9 and CEA in patients with GC. 1692 patients with GC who underwent gastrectomy were divided into the training (from January 2005 to December 2011, n = 1024) and the validation (from January 2012 to December 2013, n = 668) cohorts. Positive groups of CA125 (> 13.72 U/ml), CA19-9 (> 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 31 publications
7
42
0
Order By: Relevance
“…However, in patients with stage IV gastric cancer, CTM positivity significantly correlated with the serum CA125 level. In a previous study, serum CA125 is identified as an independent prognostic factor in patients with gastric cancer [40]. CA125 is also known as the mucin MUC16.…”
Section: Discussionmentioning
confidence: 94%
“…However, in patients with stage IV gastric cancer, CTM positivity significantly correlated with the serum CA125 level. In a previous study, serum CA125 is identified as an independent prognostic factor in patients with gastric cancer [40]. CA125 is also known as the mucin MUC16.…”
Section: Discussionmentioning
confidence: 94%
“…As for possible explanations of the gap of CEA levels between GC tissues and the sera, there have been several reports that the amount of CEA released into the circulation does not depend mainly on the tissue CEA level, but depends on distribution patterns within the cancerous tissues, tumor differentiation and lymphovascular invasion [29][30][31] ducted immunohistochemical analysis and found that the appearance of CEA in the surrounding stroma led to the elevation of blood CEA levels due to the abnormal distribution of CEA on the basolateral plasma membrane of colorectal cancer cells [32]. Although previous studies demonstrated that CEA-producing GC and CA19-9-producing GC have different characteristics in morphology, histopathology and metastatic preference, the prognostic values of serum CEA and CA19-9 are still under debate [5,6,9,14].…”
Section: Discussionmentioning
confidence: 99%
“…Whether serum CEA and CA19-9 levels contribute as prognostic indicators for patients with GC has long been discussed, but the results have been rather mixed [10,11]. Inconsistencies in the criteria used for patient inclusion and analyses and different variables (e.g., early detection or prognostic factors) are cited as possible explanations of the conflicting data [12][13][14]. In addition, advances in measurement technology, increased prevalence of early-stage GC, and changes in standard of care such as application of adjuvant therapies may also have caused changes in the clinical significance of serum CEA and CA19-9 over time [15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from India showed a sensitivity of 42% and a negative predictive value of 63.29% for CA 19-9 in GC [32]. In a more recent study, Wang et al [33] enrolled more than 1,600 patients with GC who underwent gastrectomy and were divided into training and validation cohorts. They discovered positive rates of 20.0, 42.3, and 19.2% for preoperative CA 19-9, CA 125, and CEA, respectively.…”
Section: Ca 19-9 In Gcmentioning
confidence: 99%